2023
DOI: 10.3389/fmicb.2023.1195096
|View full text |Cite
|
Sign up to set email alerts
|

Mixed oligosaccharides-induced changes in bacterial assembly during cucumber (Cucumis sativus L.) growth

Abstract: The application of oligosaccharides can promote plant growth by increasing photosynthesis or inducing plant innate immunity. However, the mechanisms by which oligosaccharides affect bacterial community diversity and abundance remain unclear. In this study, a mixed oligosaccharide was applied to the growth of cucumbers. The findings of the present study suggest that the application of MixOS has significant effects on the bacterial communities in the phyllosphere, rhizosphere, and bulk soil of cucumber plants. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 43 publications
0
0
0
Order By: Relevance
“…Choudhary et al [32] proposed that the growth-promoting effects of copper-chitosan nanoparticles could boost maize resistance to Curvularia leaf spot by increasing leaf chlorophyll content and maintaining normal physiological processes, and even facing abiotic stress. Similarly, CSOS and MixOS treatments significantly increased the leaf SPAD of both crops (Figure 2), where the increases in strawberry leaves were consistent with Metwaly et al [7], and the increases in cucumber leaves were consistent with Tan et al [11] and Wang et al [8], when exposed to oligosaccharides. Additionally, the SPAD values were positively correlated with the total yield of strawberry and individual fruit weight of cucumber (Table 3), indicating that spraying the two tested oligosaccharides had a promotional effect on yield through increasing chlorophyll content.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Choudhary et al [32] proposed that the growth-promoting effects of copper-chitosan nanoparticles could boost maize resistance to Curvularia leaf spot by increasing leaf chlorophyll content and maintaining normal physiological processes, and even facing abiotic stress. Similarly, CSOS and MixOS treatments significantly increased the leaf SPAD of both crops (Figure 2), where the increases in strawberry leaves were consistent with Metwaly et al [7], and the increases in cucumber leaves were consistent with Tan et al [11] and Wang et al [8], when exposed to oligosaccharides. Additionally, the SPAD values were positively correlated with the total yield of strawberry and individual fruit weight of cucumber (Table 3), indicating that spraying the two tested oligosaccharides had a promotional effect on yield through increasing chlorophyll content.…”
Section: Discussionsupporting
confidence: 82%
“…Chitosan promoted individual fruit weight and total fruit weight per plant, and ultimately elevated total yield by 42% when sprayed on strawberry [6]. Wang et al [8] observed an increase in the total yield of cucumber in the MixOS group. As demonstrated in our study (Table 2), MixOS spraying significantly increased the individual fruit weight and total fruit number per plant of the strawberry and elevate the single fruit weight and total fruit weight per plant of the cucumber, ultimately promoting the total yield of both crops.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations